Peran Keluarga Dan Motivasi Ibu Terhadap Pemberian Asi Eksklusif Pada Ibu Menyusui - Indra, Dewi; Hardono, Hardono (Universitas Aisyah Pringsewu (UAP) Lampung, 2021)
Breastmilk is ideal food for babies that is safe, clean, contains antibodies and can protect against many common childhood diseases. In Tanggamus Regency, it was still found that 25% of mothers do not exclusively breastfeed their babies. The research type used is quantitative and the research design is cross-sectional. The samples were primiparous breastfeeding mothers who had babies aged 7-12 months in Pariaman Village as many as 33 respondents. The univariate analysis used frequency distribution and bivariate analysis used Chi-square. The results of the univariate analysis revealed that the respondents who gave exclusive breastfeeding were 26 (78.8%), the good family role as 27 (81.8%), high motivation for breastfeeding mothers were 17 (51.51%). Bivariate analysis revealed that there was no correlation between the family role on giving exclusive breastfeeding (p-value 1,000 less than 0.05). There was a significant correlation between mother's motivation on giving exclusive breastfeeding (p-value 0.039 less than 0.05) and OR = 0.104, it means that the mothers with high motivation have 0.104 times the opportunity to give exclusive breastfeeding compared to mothers with low motivation. It is expected that health workers will regularly provide education to breastfeeding mothers so, they can increase motivation in giving exclusive breastfeeding for their babies.